Formação inicial de professores para a docência com bebês: o caso do Curso de Pedagogia da FACED-UFC - Rodrigues, Ana Paula Cordeiro Marques (2018)
The present research arose of the concern and necessity of to inquire the teachers initial formation to the teaching with babies (children from zero to eighteen months), a thematic that has gained visibility in the last years, but still occupy a small space in the academic production. The principal research objective was to analyse the presential pedagagic course contributions offered by Faculdade de Educação da Universidade Federal do Ceará (FACED-UFC) to the teaching with babies, from of the teaching perspectives, students and course graduates. For this, were used of the knowledges about the teachers formation to infantil education and about the babies education, specially the studies realized by Barbosa (2010), Barbosa and Fochi (2015), Cruz (2000), Kishimoto (2005), Oliveira-Formosinho (2001), among others autours. Having as option the qualitative research approach, were used as techniques to data construction the questionnaires application and the Semi-structured interview. Participated of the interviews the total of three teachers, nineteen final semesters students of the daytime and nighttime pedagogy course and six graduates of this college that acted or act as babies teacher. For the data record were used a voice recorder and a field journal. The data analysis revealed that the formation offered in the FACED-UFC presential pedagogy course does not contemplate effectively the complexity and the peculiarities of the teacher practice with babies. Although the majority of subjects to recognize the good formation to the infantile education teaching and some initiatives related to the pedagogical practices with babies effected over the past two years, they considered that yet are offered few opportunities, inside and outside of the course curriculum, that enable to the pedagogy students the appropriation of important themes related to the babies and their educational processes. Thus, it was possible to identify a frailties serie that limit the quality of the initial formation aiming to the teaching with babies in the FACED-UFC pedagogy course and also some alternatives in the sense of overcome this frailties. The subjects three groups interviews set analysis offers important elements to enrich the debates about the curriculum elaboration and reformulation to the pedagogy course and in the case of the focused course in the present research, indicates the urgency of changed in this curriculum so that the futures pedagogy graduates formed in this college have the necessary subsidies theoretical and practical to develop a quality teaching with the babies.